Analisis RCA dan RSCA di Negara China (Impor) dan Rusia (Ekspor) pada Komoditas Gas Alam - Adinda Nurhalizah; Dia Ayu Rifatus Sholikah; Dwi Meilinda Putri; Fahrizal Taufiqqurrachman (INDO PUBLISHING, 2026)
Natural gas trade plays a strategic role in the global trading system and is crucial for ensuring energy security. Russia is recognized as one of the world’s largest exporters of natural gas, while China has become a major importer due to rapid economic growth and industrial expansion. This study aims to analyze the competitiveness of natural gas trade between Russia as an exporting country and China as an importing country using a quantitative approach. The analytical methods applied include Revealed Comparative Advantage (RCA) and Revealed Symmetric Comparative Advantage (RSCA) to measure comparative advantage, as well as the Trade Specialization Index (TSI) as a supporting analysis to identify trade specialization patterns. This study utilizes secondary data on international natural gas trade analyzed through descriptive quantitative methods. The results indicate that Russia consistently records RCA values greater than one and positive RSCA values, reflecting strong comparative advantages in natural gas exports. In contrast, China shows RCA values below one and negative RSCA values, confirming its role as a natural gas importing country. The TSI analysis further supports these findings by positioning Russia in export specialization and China in import specialization